Country-Wise Forecast Model for the Effective Reproduction Number Rt of Coronavirus Disease - Medina-Ortiz, David; Contreras, Sebastián; Barrera-Saavedra, Yasna; Cabas-Mora, Gabriel; Olivera-Nappa, Álvaro (Frontiers in Physics, 2020)
Due to the particularities of SARS-CoV-2, public health policies have played a crucial role in the control of the COVID-19 pandemics. Epidemiological parameters for assessing the stage of the outbreak, as the Effective Reproduction Number (R_t), are not always straightforward to calculate, thus raising barriers between the scientific community and non-scientific decision-making actors. The combination of estimators of R_t with elaborated Machine Learning-based forecasting techniques provides a way to support decision-making when assessing governmental plans of action. In this work, we develop forecast models applying logistic growth strategies and auto-regression techniques based on Auto-Regressive Integrated Moving Average (ARIMA) models for each country that record information about the COVID-19 outbreak. Using the forecast for the main variables of the outbreak, namely the number of infected (I), recovered (R), and dead (D) individuals, we provide a real-time estimation of R_t and its temporal evolution within a timeframe. With such models, we evaluate R_t trends at the continental and country level, providing a clear picture of the effect governmental actions have had on the spread. We expect this methodology of combining forecast models for raw data to calculate R_t to serve as valuable input to support decision-making related to controlling the spread of SARS-CoV-2.